Porphyrins containing basic aliphatic amino groups as potential broad-spectrum antimicrobial agents - Scanone, Ana Coral (2018)
New porphyrin derivatives bearing basic aliphatic amino groups were synthesized from the condensation of meso-4-[(3-N,N-dimethylaminopropoxy)phenyl]dipyrromethane, pentafluorobenzaldehyde and 4-(3-N,N-dimethylaminopropoxy)benzaldehyde. The reaction was catalyzed by trifluoroacetic acid in acetonitrile. This approach was used to obtain porphyrins with different patterns of substitution, of which three of them were isolated: 5,15-di(4-pentafluorophenyl)-10,20-di[4-(3-N,N-dimethylaminopropoxy)phenyl]porphyrin (F10APP), 5-(4-pentafluorophenyl)-10,15,20-tris[4-(3-N,N-dimethylaminopropoxy)phenyl]porphyrin (F5APP) and 5,10,15,20-tetrakis[4-(3-N,N-dimethylaminopropoxy)phenyl]porphyrin (TAPP). The UV–vis spectroscopic characterizations and the photodynamic effect of these compounds were compared in N,N-dimethylformamide. These porphyrins showed red fluorescence emission with quantum yields of 0.09-0.15. Moreover, they sensitized the production of singlet molecular oxygen, reaching quantum yields values of 0.33-0.53. Photodynamic inactivation was studied in two bacteria, Staphylococcus aureus and Escherichia coli, and a yeast Candida albicans. High amount of cell-bound porphyrin was obtained at short times (<2 min) of incubation. After 15 min irradiation, a 7 log reduction of S. aureus was found for cells treated with 1 μM F5APP. Similar photokilling was obtained in E. coli, but using 7.5 μM F5APP and 30 min irradiation. Under these conditions, a decrease of 5 log was observed in C. albicans cells. An increase in cell survival was observed by addition of sodium azide, whereas a slight protective effect was found in the presence of D-mannitol. Moreover, the photoinactivation mediated by these porphyrins was higher in D2O than in water. Thus, these porphyrins induced the photodynamic activity mainly through the intermediacy of O2(1Δg). In particular, F5APP was a highly effective photosensitizer with application as a broad-spectrum antimicrobial. This porphyrin contains three basic aliphatic amino groups that may be protonated at physiological pH. In addition, it is substituted by a lipophilic pentafluorophenyl group, which confers an amphiphilic character to the tetrapyrrolic macrocycle. This effect can increase the interaction with the cell envelopment, improving the photocytotoxic activity against the microorganisms.